2010
DOI: 10.1158/1055-9965.epi-10-0543
|View full text |Cite
|
Sign up to set email alerts
|

Body Size, Weight Change, and Risk of Colon Cancer

Abstract: Background: Epidemiologic studies have consistently reported positive associations between obesity and colon cancer risk for men, but the evidence is less consistent for women. Few studies have investigated effects of weight change on colon cancer risk.Methods: Using the Melbourne Collaborative Cohort Study, which recruited men and women mostly in 40 to 69 years of age, we investigated associations between weight and body mass index (BMI) at age 18 years and at study entry and weight change since age 18 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 57 publications
4
58
0
1
Order By: Relevance
“…Among women with available BMI measurements, there was no significant association between BMI level and cancer of digestive organs (p = 0.805) or hematological malignancies (p = 0.305). Similarly, previous studies have shown that among women, unlike in men, there is no [47] or little [48] association between body mass index and the aforementioned cancers. Therefore, it is unlikely that missing BMI measurements significantly biased our results.…”
Section: Discussionsupporting
confidence: 63%
“…Among women with available BMI measurements, there was no significant association between BMI level and cancer of digestive organs (p = 0.805) or hematological malignancies (p = 0.305). Similarly, previous studies have shown that among women, unlike in men, there is no [47] or little [48] association between body mass index and the aforementioned cancers. Therefore, it is unlikely that missing BMI measurements significantly biased our results.…”
Section: Discussionsupporting
confidence: 63%
“…Obesity, physical inactivity and the "Western diet" are all risk factors associated with an increased risk for CRC. The prevalence of obesity has increased markedly in the United States and is a major risk factor for CRC (14)(15)(16). Physical activity has been demonstrated to reduce the risk of both colon and rectal cancer (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…*Self-reported past body weight has 64-95% correlation with actual weight. 27 environment for transformed cell proliferation and lack of apoptosis. 2,35 Current screening guidelines do not recommend screening diabetics or obese patients earlier, though they do note that obese patients are at a greater risk.…”
Section: Type 2 Diabetes Mellitus (Dm2)mentioning
confidence: 99%